Hochgenaue radarbasierte Abstandsmessung mit geführter Wellenausbreitung - Ayhan, Serdal (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2016)
In this work, a new measurement approach for a radar-based high accuracy distance measurement with guided wave propagation is presented. The reached distance accuracy is in the single-digit range. The main influencing factors on the achievable accuracy are characterized with the developed methods and techniques, to allow a systematic design and optimization of the system in advance.